PARAMETERISASI PENGONTROL SUBOPTIMAL HOO - Rahman Hakim, Arif
Abstract : Designing control system using H., Controller yields a high-order controller, meanwhile a high-order controller in implementation is impractical. Therefore, the reduced-order controller is considered. One of the ways to get the lower-order controller is by using controller parameterization. It using Game Riccati Equation (GRE) technique. In this case we use the suboptimal controller, since the optimal controller is dificult to get. The advantage of this paramaterization is numerically simpler to apply. Furthermore, with this parameterizazion central controller can be derived.